2002
DOI: 10.1515/bc.2002.104
|View full text |Cite
|
Sign up to set email alerts
|

N-Hydroxyarylamine O-Acetyltransferase-Deficient Escherichia coli Strains Are Resistant to the Mutagenicity of Nitro Compounds

Abstract: In Salmonella typhimurium, a single enzyme catalyzes both the acetyl CoA-dependent O-acetylation of hydroxylamines (a key step in the activation of mutagenic nitroaromatic compounds and related aromatic and heterocyclic amines) and the N-acetylation of aromatic amines. S. typhimurium Ames test mutants lacking this activity are highly resistant to the genotoxic effects of nitro compounds. However, such mutants have not yet been obtained in Escherichia coli. We used a PCR-based method to engineer a null mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In bacteria, mutagenic nitroaromatic compounds, such as 2‐nitrofluorene (2‐NF) and 2‐nitro‐3,4‐dimethylimidazo[4,5‐f]quinoline, are reduced to hydroxyarylamines by nitroreductases, then O ‐acetylation of hydroxyarylamines by NhoA yields highly reactive N ‐acetoxy esters, which undergo spontaneous heterolysis, generating DNA adducts . Thus, activity of NhoA is necessary for the mutagenicity of nitroaromatic compounds in bacteria, and previous studies revealed that nhoA ‐deficient bacteria are resistant to the mutagenicity of nitro compounds .…”
Section: Resultsmentioning
confidence: 99%
“…In bacteria, mutagenic nitroaromatic compounds, such as 2‐nitrofluorene (2‐NF) and 2‐nitro‐3,4‐dimethylimidazo[4,5‐f]quinoline, are reduced to hydroxyarylamines by nitroreductases, then O ‐acetylation of hydroxyarylamines by NhoA yields highly reactive N ‐acetoxy esters, which undergo spontaneous heterolysis, generating DNA adducts . Thus, activity of NhoA is necessary for the mutagenicity of nitroaromatic compounds in bacteria, and previous studies revealed that nhoA ‐deficient bacteria are resistant to the mutagenicity of nitro compounds .…”
Section: Resultsmentioning
confidence: 99%
“…BLAST analysis based on the amino acid sequences showed that both NhoA1 and NhoA2 belong to the family of N-hydroxyarylamine O-acetyltransferases (NhoAs). Members of the NhoAs have been previously found to catalyze the acetylation of mutagenic and carcinogenic N-hydroxyarylamines that are formed by reduction of nitroarenes or by oxidation of aromatic amines (18,(21)(22)(23)(24). However, whether NhoAs of Enterobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Strain DJ2002 [37] was constructed by PCR-mediated deletion of the nhoA gene, which encodes the endogenous E. coli NAT, and serves as a NAT − control. Strains DJ701 and DJ702 [38] bear plasmid pNM12 [39] and express the Salmonella typhimurium NAT enzyme at high levels.…”
Section: Methodsmentioning
confidence: 99%